A multicenter retrospective study evaluating the impact of desmopressin on hematoma expansion in patients with antiplatelet-associated intracranial hemorrhage. Issue 222 (February 2023) - Summers, Amanda; Singh, Jasmeet; Lai, Michelle; Schomer, Kendra J.; Martin, Ryan; Vitt, Jeffrey R.; Derry, Katrina L.; Box, Kevin; Chu, Frank; Arias, Valerie; Minokadeh, Anushirvan; Stern-Nezer, Sara; et al.
Abstract: Introduction: Antiplatelet medications interfere with hemostasis which can contribute to increased risk of hematoma expansion and potentially worse outcomes in patients presenting with intracranial hemorrhages (ICH). Current Neurocritical Care Society guidelines recommend desmopressin (DDAVP) in patients with antiplatelet-associated ICH with evidence limited by small cohorts. Materials and methods: Patients were included in our multi-center, retrospective study if they had computed tomographic (CT) scan confirmed ICH and were taking antiplatelet medications. Patients were excluded if hospital length of stay was <24 h, administered DDAVP dose was <0.3 μg/kg, no follow-up head CT scan was performed within the first 24 h after baseline, major neurosurgical intervention was performed in between CT scans, or the injury was an acute on chronic ICH. The primary outcome was incidence of hematoma expansion (defined as >20 % increase from baseline). Secondary outcomes were incidence of thrombotic complications within 7 days, largest absolute decrease in serum sodium within the first 24 h, and patient disposition. Results: Among the 209 patients included in the study, 118 patients received DDAVP while 91 did not. The frequency of hematoma expansion was similar between patients who received DDAVP and those who did not (16.1 % vs 17.6 %; P = 0.78). No difference in secondary outcomes was observed between the two groups. Conclusions: These findings in conjunction with recently published literature may suggest minimal benefit or harm with DDAVP treatment. However, further study could elucidate any potential impact on long-term function outcomes. Highlights: This study sought to analyze the safety and efficacy of DDAVP in patients with antiplatelet-associated ICH. Primary outcome of hematoma expansion incidence was determined by review of CT scans within 24 hours of the baseline scan. Administration of DDAVP did not reduce incidence of hematoma volume expansion in patients with antiplatelet-associated ICH. Future prospective randomized controlled studies are needed to evaluate the efficacy of DDAVP in antiplatelet associated ICH.